Aging Affects KV7 Channels and Perivascular Adipose Tissue-Mediated Vascular Tone - Wang, Yibin; Yildiz, Fatima; Struve, Andrey; Kassmann, Mario; Markó, Lajos; Köhler, May-Britt; Luft, Friedrich C.; Gollasch, Maik; Tsvetkov, Dmitry (Frontiers in Physiology, 2021)
Aging is an independent risk factor for hypertension, cardiovascular morbidity, and mortality. However, detailed mechanisms linking aging to cardiovascular disease are unclear. We studied the aging effects on the role of perivascular adipose tissue and downstream vasoconstriction targets, voltage-dependent KV7 channels, and their pharmacological modulators (flupirtine, retigabine, QO58, QO58-lysine) in a murine model. We assessed vascular function of young and old mesenteric arteries in vitro using wire myography and membrane potential measurements with sharp electrodes. We also performed bulk RNA sequencing and quantitative reverse transcription polymerase chain reaction tests in mesenteric arteries and perivascular adipose tissue to elucidate molecular underpinnings of age-related phenotypes. Results revealed impaired perivascular adipose tissue-mediated control of vascular tone particularly via KV7.3-5 channels with increased age through metabolic and inflammatory processes and release of perivascular adipose tissue-derived relaxation factors. Moreover, QO58 was identified as novel pharmacological vasodilator to activate XE991-sensitive KCNQ channels in old mesenteric arteries. Our data suggest that targeting inflammation and metabolism in perivascular adipose tissue could represent novel approaches to restore vascular function during aging. Furthermore, KV7.3-5 channels represent a promising target in cardiovascular aging.